2022
DOI: 10.1055/a-1770-7353
|View full text |Cite
|
Sign up to set email alerts
|

The influence of computer-aided polyp detection systems on reaction time for polyp detection and eye gaze

Abstract: Background and study aims: Multiple computer-aided systems for polyp detection (CADe) are currently introduced into clinical practice, with an unclear effect on examiner behavior. In this work, we aimed to measure the influence of a CADe system on reaction time, mucosa misinterpretations, and changes in visual gaze pattern. Patients and methods: Participants with variable levels of experience in colonoscopy examined video sequences while eye movement was tracked. Using a crossover design, videos were presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Another possibility would be to investigate (e.g. by eye‐tracking) whether the examiner's attention could be better focused on the intervention by reducing distracting CADe signals 17 . Other limitations include that, to facilitate the generation of a large‐annotated training dataset in a short period of time, no predefined protocol was used for video selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility would be to investigate (e.g. by eye‐tracking) whether the examiner's attention could be better focused on the intervention by reducing distracting CADe signals 17 . Other limitations include that, to facilitate the generation of a large‐annotated training dataset in a short period of time, no predefined protocol was used for video selection.…”
Section: Discussionmentioning
confidence: 99%
“…whether the examiner's attention could be better focused on the intervention by reducing distracting CADe signals. 17 CADe systems already achieved a remarkable benefit in randomized controlled trials. Future developments of those systems include improving usability by adding customizable features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the authors concluded that more data for non-Asian populations is necessary. Furthermore, examiners focus on the center of the endoscopic image and CADe systems improve detection in the image’s periphery [ 9 ]. Lastly, to our knowledge there is no data regarding usability and acceptance of CADe systems in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the second paper, Troya et al tracked the eye movement for polyp detection, analyzing its interaction with a computeraided polyp detection system (CADe) [2]. Novice endoscopists, which may approximate low detectors, showed a trend for a slower reaction time in polyp detection by nearly 1 second compared with experienced endoscopists.…”
mentioning
confidence: 99%